2019
DOI: 10.1002/eqe.3214
|View full text |Cite
|
Sign up to set email alerts
|

How is collapse risk of RC buildings affected by the angle of seismic incidence?

Abstract: Summary Despite the undeniable influence of the angle of seismic incidence on seismic demand, limited research has been performed to determine its effect when assessing the probabilistic seismic performance of a structure. Since the ground motion group size has a well‐known significant effect on the variability of collapse risk, the joint effect of both the ground motion group size and the angle of seismic incidence on the estimation of collapse risk is investigated. Results show that the two variables have a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…These parameters could have different values. Other researchers (Celarec et al 2012;Martinelli et al 2015;Jeon et al 2015;Mohammad et al 2016;Landi et al 2016;Noh et al 2017;Huang et al 2018aHuang et al , 2018bSkoulidou et al 2019aSkoulidou et al , 2019b adopted the uniaxial material models available in the OpenSees software to model the hysteretic response of infill walls. The strength of the Hysteretic material in a positive direction was input as the minimum value to represent the negligible tensile strength of the infill walls to bounding frames.…”
Section: Existing Phenomenological Models Of Infill Wallsmentioning
confidence: 99%
See 1 more Smart Citation
“…These parameters could have different values. Other researchers (Celarec et al 2012;Martinelli et al 2015;Jeon et al 2015;Mohammad et al 2016;Landi et al 2016;Noh et al 2017;Huang et al 2018aHuang et al , 2018bSkoulidou et al 2019aSkoulidou et al , 2019b adopted the uniaxial material models available in the OpenSees software to model the hysteretic response of infill walls. The strength of the Hysteretic material in a positive direction was input as the minimum value to represent the negligible tensile strength of the infill walls to bounding frames.…”
Section: Existing Phenomenological Models Of Infill Wallsmentioning
confidence: 99%
“…FEMA356 (2000), Al-Chaar (2002), Mostafaei and Kabeyasawa (2004) and Liberatore et al (2018) developed different force-displacement envelope models for the equivalent strut, but did not define the unloading and reloading branches. Recently, many researchers (Celarec et al 2012;Martinelli et al 2015;Jeon et al 2015;Mohammad et al 2016;Landi et al 2016;Noh et al 2017;Huang et al 2018aHuang et al , 2018bSkoulidou et al 2019aSkoulidou et al , 2019b have simulated the behaviour of infill walls with the help of some existing materials available in the OpenSees software, such as the Hysteretic and Concrete01 materials. Most of these approaches could capture the backbone curves of infill walls, but failed to accurately account for the hysteretic responses of the infill walls under cyclic loading.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of specific code provisions with regard to the axes of the strong motion input leads to the application of the horizontal earthquake components along the structural axes of the buildings. This common engineering practice can result in significant underestimation of seismic demands (Athanatopoulou [2]; Rigato and Medina [3]; Kostinakis et al [4][5][6][7]; Fontara et al [8]; Pavel and Nica [9]; Cavdar and Ozdemir [10]; Skoulidou et al [14]; Lucchini et al [43]; Nguyen and Kim [44]; Roy et al [45]).…”
Section: The Influence Of Incident Angle On the Seismic Response Of Rc Buildingsmentioning
confidence: 99%
“…Cavdar and Ozdemir [10] examined the change in response of a seismically isolated structure as a function of ground motion orientation and they showed that using the maximum direction of ground motions does not lead to the maximum response compared to the one obtained by considering different orientations of seismic records. The issue of the seismic motion's orientation from a probabilistic point of view was also investigated by a number of researchers (Lagaros [11]; Giannopoulos and Vamvatsikos [12]; Vargas et al [13]; Skoulidou et al [14]; Skoulidou and Romão [15]), who tried to evaluate the impact of the angle of seismic incidence on the buildings' risk.…”
Section: Introductionmentioning
confidence: 99%
“…Despite such evidence, the incidence angle effect is not systematically considered in estimates of seismic risk. It has been argued that when the orientation of a structure's principal axes relative to the seismic rupture is unknown, e.g., due to limited information on the building, or high variability of the location of the rupture itself, it is computationally more efficient to only consider a single random orientation per ground motion record employed 16,17 . This article is aimed at developing a simplified procedure to account for the effect of directionality by offering a baseline approach for bias‐correcting fragility functions of structures.…”
Section: Introductionmentioning
confidence: 99%